Gastrointestinal Microbiota and Some Children Diseases: A Review. (30th October 2012) - Weber, Thabata Koester; Polanco, Isabel
Abstract : The bacterial colonization is defined immediately after birth, through direct contact with maternal microbiota and may be influenced during lactation. There is emerging evidence indicating that quantitative and qualitative changes on gut microbiota contribute to alterations in the mucosal activation of immune system leading to intra- or extra-intestinal diseases. A balance between pathogenic and beneficial microbiota throughout childhood and adolescence is important to gastrointestinal health, including protection against pathogens, inhibition of pathogens, nutrient processing (synthesis of vitamin K), stimulation of angiogenesis, and regulation of host fat storage. Probiotics can promote an intentional modulation of intestinal microbiota favoring the health of the host. This paper is a review about modulation of intestinal microbiota on prevention and adjuvant treatment of pediatric gastrointestinal diseases.